Vloga čustvenčkov in čustvenih simbolov pri socialnem inženiringu - Fujs, Damjan (Psihološka obzorja (Ljubljana), 2020)
The purpose of this paper is to place the use of emojis and emoticons in communication, e.g., on social networks and with SMSs, to the field of social engineering. With a systematic literature survey in academic databases Web of Science and Scopus, and opportunistic search, 40 scientific papers about emojis and emoticons in social engineering were identified. The use of emojis and emoticons in communication is a form of direct communication as the sender directly influences the recipient. Emojis and emoticons are a universal tool that is understood by all communication technology users regardless of their demographics. Most of the analyzed studies employ a quantitative approach and span different research areas, such as marketing, psychology, sociology, etc. This paper represents one of the first systematic literature reviews that deal with emojis and emoticons in the context of social engineering. The findings of this paper may serve as a basis for further, especially qualitative research.
Keywords: communication; čustvenčki; čustveni simboli; družbeni inženiring; emojis; komunikacija; persuasion; phishing; prepričevanje; ribarjenje; social engineering; spletno ribarjenje